Systemic barriers and opportunities for implementing school-based social–emotional learning interventions in low-income and conflict-affected settings - McCoy, Dana Charles; Hanno, Emily C. (Frontiers in Psychology, 2023)
Children living in low-income and conflict-affected settings face unique systemic risk factors that shape their social, emotional, and mental well-being. However, little is known about how these and other systemic factors may impede or support the delivery of social-emotional learning (SEL) interventions in these contexts. In this article, we draw from our experience delivering and evaluating a classroom-based SEL curriculum in Rio de Janeiro, Brazil to surface systemic barriers and opportunities for implementing SEL interventions in low-income, conflict-affected settings. Specifically, we identify (1) culture, (2) timing, and (3) government support and stability as factors underlying SEL program demand, dosage, quality, and effectiveness. We provide recommendations for improving implementation of SEL programs in low-income and conflict-affected contexts, including the importance of building pro-active partnerships, using qualitative research, and investing in adaptation to both understand and address systemic barriers.